Preparation method and application of manganese-based phosphate positive electrode material with high specific energy and high stability

By preparing the carbon-coated NASICON phosphate positive electrode material Na4-aMnCrxTiyMz(PO4)3, the problem of insufficient energy density and cycle life of the positive electrode material of sodium ion battery is solved by using multi-electron reaction and high redox potential, and the effects of high energy density and long cycle life are achieved.

CN119591072APending Publication Date: 2025-03-11UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411665549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have low energy density, slow reaction kinetics, insufficient cycle life, and difficult to meet the needs of high energy density and long life.

Method used

A high specific energy and high stability manganese-based phosphate positive electrode material is prepared by adding a manganese source, a titanium source, a chromium source, a doped metal ion source, a sodium source and a phosphorus source to a citric acid solution, and after stirring, evaporation, drying and calcining, a carbon-coated NASICON phosphate positive electrode material Na4-aMnCrxTiyMz(PO4)3 is prepared.

Benefits of technology

This material achieves high energy density and long cycle life through the multi-electronic reaction of Mn2+/Mn3+/Mn4+, Cr3+/Cr4+ and Ti3+/Ti4+ electric pairs, and has excellent application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591072A_ABST
    Figure CN119591072A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a high-specific-energy and high-stability manganese-based phosphate positive electrode material, and belongs to the technical field of sodium-ion batteries. Comprising the following steps: 1) preparing a citric acid solution, adding transition metal raw materials, namely a manganese source, a titanium source, a chromium source and a doped metal ion source, into the citric acid solution, and stirring for 20-40 minutes to completely dissolve and fully complex; then adding a sodium source and a phosphorus source, and continuously stirring for 40-60 minutes to obtain a uniform solution; 2) stirring the solution in a hot water bath until gel is formed, then placing the gel in an air dry oven to completely remove the solvent, and grinding to obtain precursor powder; 3, the precursor powder is placed in a tubular furnace, high-temperature calcination is conducted under inert atmosphere protection, and the manganese-based phosphate positive electrode material.The preparation method has the advantages that the preparation process is simple and easy to operate, conditions are controllable, repeatability is good, and the sodium-ion battery positive electrode material shows the characteristics of high energy density and long cycle life and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of a high-specific-energy and high-stability manganese-based phosphate positive electrode material. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles and electronic devices due to their high energy density and long cycle life. However, the low reserves and uneven distribution of lithium resources have restricted the further development of lithium-ion batteries. In contrast, sodium-ion batteries have natural abundance and price advantages and are expected to become an important supplement to lithium-ion batteries. However, the standard electrode potential of sodium is higher than that of lithium, and its ion radius is large and its mass is heavy, resulting in low energy density, slow reaction kinetics, and insufficient cycle life of sodium-ion batteries. The positive electrode material is a key component that determines the cost and performance of the battery, so the development of high-specific energy and long-life positive electrode materials will help push the industrialization of sodium-ion batteries into the fast lane.

[0003] Among the several mainstream sodium storage cathode materials reported so far, polyanion compounds have attracted widespread attention due to their stable open framework structure that can provide a fast sodium ion transport channel. Our research group reported a micro-nanostructured polyanion NaFePO 4 Positive electrode, theoretical specific capacity up to 154 mAh g -1 , but the low working potential (about 2.5V) severely limits its energy density (YC Liu, N. Zhang, FF Wang, et al. Approaching the Downsizing Limit of Maricite NaFePO 4 toward High-Performance Cathode for Sodium-Ion Batteries,Advanced Functional Materials, 2018,28:1801917).

[0004] In order to obtain a polyanion cathode with high working voltage, Professor Chen Weihua's research group reported a Na 2.26 Fe 1.87 (SO 4 ) 3 The positive electrode has a significant improvement in output voltage (discharge voltage is 3.75 V), but is limited by the low number of transferred electrons (<2 electrons), and the discharge capacity is only 101.3 mAh g -1, the energy density has not yet been improved to the level of practical use (JYZhang, YLYan, X.Wang, et al. Bridging multiscale interfaces for developing ionically conductive high-voltage iron sulfate-containing sodium-based battery positive electrodes, Nature Communications, 2023, 14: 3701).

[0005] In 2020, our research group reported a sodium fast ion conductor (NASICON) type phosphate cathode material Na 4 MnCr(PO 4 ) 3 , activating a reversible 3-electron reaction, achieving both high voltage and high capacity, with an energy density of 566.5Wh kg -1 , which is comparable to commercial lithium iron phosphate. However, the large volume change during charge and discharge leads to unsatisfactory cycle performance, affecting its application prospects (J. Zhang, YC Liu, XD Zhao, et al. A Novel NASICON-Type Na 4 MnCr(PO 4 ) 3 Demonstrating the Energy Density Record of Phosphate Cathodes for Sodium-IonBatteries, Advanced Materials, 2020,32:1906348).

[0006] Therefore, developing a new type of polyanion cathode material for sodium-ion batteries that achieves high energy density while ensuring high cycle stability is of great significance but also faces challenges. Summary of the invention

[0007] Based on the above background, the present invention provides a preparation method and application of a high specific energy and high stability manganese-based phosphate positive electrode material. A certain proportion of manganese source, titanium source, chromium source, doped metal ion source, sodium source and phosphorus source are added to a citric acid solution, and after continuous stirring and evaporation of the solvent, the solution is dried and ground into powder, and calcined in an inert atmosphere to obtain a carbon-coated sodium fast ion conductor (NASICON) type phosphate positive electrode material Na 4-a MnCr x Ti y M z (PO 4 )3 , where M is Fe 2+ Mg 2+ , Ca 2+ 、Zn 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Al 3+ , Ga 3+ 、Zr 4+ One or more of the following; wherein the restriction conditions of each variable are 0.2≤x≤0.6; 0.4≤y≤0.8; 0<z≤0.1; x+y+z=1; a is the variable of Na content after ion doping substitution, 0.3≤a≤0.8.

[0008] The advantages of the present invention are: the preparation process is simple and easy to operate, the conditions are controllable, and the repeatability is good. 2+ / Mn 3+ / Mn 4+ The multi-electron reaction of the couple provides high capacity, Cr 3+ / Cr 4+ The high redox potential of the electrode pair increases the working voltage, Ti 3+ / Ti 4+ The electric couple stabilizes the material structure during the electrochemical cycle, while the doping ions provide additional capacity or improve the stability of the material. Therefore, this type of sodium ion battery cathode material exhibits the characteristics of high energy density and long cycle life, and has excellent application prospects.

[0009] Based on the above purpose, the present invention provides the following technical solutions:

[0010] A method for preparing a high-specific-energy and high-stability manganese-based phosphate positive electrode material comprises the following steps:

[0011] 1) preparing a citric acid solution, wherein citric acid is used as a complexing agent and a carbon source; adding a certain proportion of transition metal raw materials, namely, a manganese source, a titanium source, a chromium source and a doped metal ion source, to the citric acid solution, stirring for 20-40 minutes to completely dissolve and fully complex them; then adding a sodium source and a phosphorus source, and continuing to stir for 40-60 minutes to obtain a uniform solution;

[0012] 2) stirring the above solution in a hot water bath until a gel is formed, then placing the gel in a forced air drying oven to completely remove the solvent, and grinding to obtain a precursor powder;

[0013] 3) placing the precursor powder in a tube furnace and calcining it at high temperature under the protection of an inert atmosphere to obtain the manganese-based phosphate positive electrode material.

[0014] Furthermore, in the step 1), the solvent of the citric acid solution is a mixed solvent of deionized water and anhydrous ethanol, and the volume ratio of deionized water to anhydrous ethanol is 2:1; the stoichiometric ratio of citric acid to the transition metal element is (0.5-1.5):1; compared with the stoichiometric ratio in the chemical formula, the molar ratio of the sodium source is 3-5% in excess; and the stoichiometric ratio of the phosphorus source to the transition metal element is 3:2.

[0015] Furthermore, in step 1), the manganese source is at least one of manganese acetate, manganese nitrate, and manganese acetylacetonate; the titanium source is at least one of isopropyl titanate, tetraethyl titanate, and tetrabutyl titanate; the chromium source is at least one of chromium nitrate, chromium acetate, and chromium trioxide; the sodium source is at least one of sodium acetate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hydroxide, and sodium oxalate; the phosphorus source is at least one of diammonium phosphate and phosphoric acid. The doping metal ion source is at least one of acetate, nitrate, sulfate, oxalate, chloride, carbonate, and organic salt of the corresponding metal; the metal in the doping metal ion source is selected from one or more of Fe, Co, Ni, Mg, Ca, Zn, Cu, Al, Ga, and Zr.

[0016] Furthermore, in the step 2), the water bath temperature is 65-90°C; the drying temperature is 110-130°C, and the drying time is 8-12h.

[0017] Furthermore, in step 3), the inert atmosphere is a mixture of one or more of argon and nitrogen; the calcination temperature is 700-800°C, and the heating rate is 2-8°C min -1 The calcination time is 5-12 hours, and then it is naturally cooled to room temperature and taken out.

[0018] The present invention also provides a high specific energy and high stability manganese-based phosphate positive electrode material prepared by the method, wherein the material is a carbon-coated NASICON type positive electrode material Na 4-a MnCr x Ti y M z (PO 4 ) 3 , where M is the electrochemically active Fe 2+ 、Co 2+ 、Ni 2+ (further improve the positive electrode capacity) or electrochemically inactive Mg 2+ , Ca 2+ 、Zn 2+ , Cu 2+ 、Al 3+ , Ga 3+ 、Zr 4+(used to stabilize the structure); wherein the restriction conditions of each variable are 0.2≤x≤0.6; 0.4≤y≤0.8; 0<z≤0.1; x+y+z=1; a is the variable of Na content after ion doping substitution, 0.3≤a≤0.8.

[0019] The present invention also provides application of the high specific energy and high stability manganese-based phosphate positive electrode material in a sodium ion battery.

[0020] Furthermore, the positive electrode material Na 4-a MnCr x Ti y M z (PO 4 ) 3 , Super P conductive carbon or conductive carbon black, and binder sodium carboxymethyl cellulose (CMC-Na) are mixed in a mass ratio of 75:15:10, ground evenly, coated on an aluminum foil current collector, and dried to make a sodium ion battery positive electrode.

[0021] Furthermore, the positive electrode material Na 4-a MnCr x Ti y M z (PO 4 ) 3 The electrode sheet made of Super P conductive carbon or conductive carbon black and binder sodium carboxymethyl cellulose (CMC-Na) is used as the positive electrode of the sodium ion battery, and metallic sodium is used as the counter electrode with a concentration of 1 mol L -1 NaClO 4 5 vol% fluoroethylene carbonate (FEC) was added to propylene carbonate (PC) as the electrolyte, and glass fiber was used as the separator. The battery was assembled into a CR2032 button cell in a high-purity argon atmosphere glove box with water and oxygen contents less than 0.01 ppm.

[0022] Compared with the prior art, the advantages of the present invention are:

[0023] The material preparation process is simple and easy to operate, the conditions are controllable and the repeatability is good. The obtained positive electrode material makes full use of Mn 2+ / Mn 3 + / Mn 4+ The multi-electron reaction of the couple provides high capacity, Cr 3+ / Cr 4+ The high redox potential of the electrode pair increases the working voltage, Ti 3+ / Ti 4+The electric couple stabilizes the material structure during the electrochemical cycle, while the doping ions provide additional capacity or improve the stability of the material. This type of sodium ion battery cathode material exhibits high energy density and long cycle life, and has excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 It is Na obtained in Example 1 of the present invention. 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 XRD pattern of positive electrode material;

[0026] Figure 2 It is Na obtained in Example 1 of the present invention. 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 SEM, TEM and EDS Mapping images of the positive electrode material, where a is the SEM image, b is the TEM image, and c is the EDS Mapping image;

[0027] Figure 3 The Na prepared in Example 1 of the present invention 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 The charge and discharge curve and cycle performance diagram of the button battery assembled with positive electrode materials, where a is the charge and discharge curve diagram and b is the cycle performance diagram. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0029] Example 1

[0030] 1) Prepare a mixed solvent of 50 mL of deionized water and 25 mL of anhydrous ethanol, add 2 mmol of anhydrous citric acid, and stir until completely dissolved; take 1 mmol of manganese acetate tetrahydrate, 0.6 mmol of isopropyl titanate, 0.35 mmol of cadmium nitrate nonahydrate, and 0.05 mmol of aluminum nitrate nonahydrate, and add them to the above citric acid solution in sequence, and continue stirring for 30 minutes to dissolve and fully complex; then add 3.57 mmol of sodium acetate (molar excess of 5%) and 3 mmol of diammonium phosphate, and continue stirring for 60 minutes until a uniform solution is formed;

[0031] 2) Stirring the above solution in a hot water bath at 85°C to evaporate the solvent until a gel is formed, then drying the gel in a drying oven at 120°C for 10 hours to completely remove the solvent, and grinding to obtain a powder precursor;

[0032] 3) The above powder was placed in a tube furnace and heated at 4 °C min -1 The heating rate was raised to 750℃ and kept for 8h to obtain carbon-coated NASICON-type Na 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 Positive electrode material.

[0033] The Na prepared in Example 1 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 The positive electrode material is made into an electrode according to the following method:

[0034] Will Na 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 The positive electrode material is mixed with Super P conductive carbon and binder sodium carboxymethyl cellulose (CMC-Na) in a mass ratio of 75:15:10, ground evenly and coated on aluminum foil, and dried to make a positive electrode for sodium ion batteries. The metal sodium sheet is used as the counter electrode, and the concentration is 1 mol L -1 NaClO 4 5 vol% fluoroethylene carbonate was added to the PC solution as the electrolyte and glass fiber was used as the separator. The button cells with model CR2032 were assembled in a high-purity argon atmosphere glove box.

[0035] Figure 1 is Na in Example 1 of the present invention 3.4 MnCr0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 XRD spectrum of the positive electrode material. By comparing with the standard diffraction card, it is found that the prepared material has a NASICON-type rhombic hexagonal structure with a space group of R-3c. The sample diffraction peak is sharp and has no impurity peaks, proving that its crystallinity and purity are relatively high.

[0036] Figure 2 a is Na in Example 1 of the present invention 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 SEM image of the positive electrode material. This shows that the material is uniformly dispersed nanoparticles with a large specific surface area that can expose abundant active sites and effectively shorten the migration path of sodium ions; the surface of the particles is uniformly coated with amorphous carbon, which is conducive to the improvement of electronic conductivity. Figure 2 b is the HRTEM image of the material, from which it can be clearly observed that the surface of the material is covered with a carbon layer about 3 nm thick. The lattice spacing of the material is measured to be 0.38 nm, corresponding to the (113) crystal plane in the XRD results. Figure 2 c is the EDS Mapping element distribution diagram, which proves that Na, Mn, Cr, Al, Ti, P, O, and C elements are evenly distributed in the material.

[0037] Figure 3 a is Na in Example 1 of the present invention 3.4 MnCr 0.35 Ti 0.6 Al 0.05 (PO 4 ) 3 The charge and discharge curve of the positive electrode material in the sodium ion battery is shown in the figure. + / Na), the first-week discharge capacity at 0.1C current density reached 156.1mAh g -1 , showing Ti 3+ / Ti 4+ ,Mn 2+ / Mn 3+ / Mn 4+ , and Cr 3+ / Cr 4+ The redox reaction of the electrode pair is ≈2.7 electrons, the average working voltage is 3.30 V, and the energy density reaches 515 Wh kg -1 . Figure 3 b is Na 3.4 MnCr 0.35 Ti0.6 Al 0.05 (PO 4 ) 3 The positive electrode has a cycling performance of 92.3% at a rate of 0.5C after 3 weeks of activation at 0.2C. Compared with other NASICON-type phosphate positive electrodes, this material has outstanding energy density and excellent cycling performance.

[0038] Example 2

[0039] 1) Prepare a mixed solvent of 50 mL of deionized water and 25 mL of anhydrous ethanol, add 2 mmol of anhydrous citric acid, and stir until completely dissolved; take 1 mmol of manganese acetate tetrahydrate, 0.6 mmol of isopropyl titanate, 0.3 mmol of cadmium nitrate nonahydrate, and 0.1 mmol of ferrous acetylacetonate, and add them to the above citric acid solution in sequence, and continue stirring for 30 minutes to dissolve and fully complex; then add 3.675 mmol of sodium acetate (molar excess of 5%) and 3 mmol of diammonium phosphate, and continue stirring for 60 minutes until a uniform solution is formed;

[0040] 2) Stirring the above solution in a hot water bath at 85°C to evaporate the solvent until a gel is formed, then drying the gel in a drying oven at 120°C for 10 hours to completely remove the solvent, and grinding to obtain a powder precursor;

[0041] 3) The above powder was placed in a tube furnace and heated at 4 °C min -1 The heating rate was raised to 700℃ and kept for 8h to obtain carbon-coated NASICON-type Na 3.5 MnCr 0.3 Ti 0.6 Fe 0.1 (PO 4 ) 3 Positive electrode material.

[0042] The Na prepared in Example 2 3.5 MnCr 0.3 Ti 0.6 Fe 0.1 (PO 4 ) 3 The positive electrode material was assembled into a CR2032 button cell according to the method in Example 1. + / Na), the first-week discharge capacity at 0.1C current density is 152.3 mAh g -1 After activation at 0.2C for 3 weeks and cycling at 0.5C for 50 weeks, the capacity retention rate was 89.5%.

[0043] Example 3

[0044] 1) Prepare a mixed solvent of 50 mL of deionized water and 25 mL of anhydrous ethanol, add 2 mmol of anhydrous citric acid, and stir until completely dissolved; take 1 mmol of manganese acetate tetrahydrate, 0.5 mmol of isopropyl titanate, 0.4 mmol of cadmium nitrate nonahydrate, and 0.1 mmol of magnesium nitrate hexahydrate, add them to the above citric acid solution in sequence, and continue stirring for 30 minutes to dissolve and fully complex; then add 3.78 mmol of sodium acetate (molar excess of 5%) and 3 mmol of diammonium phosphate, and continue stirring for 60 minutes until a uniform solution is formed;

[0045] 2) Stirring the above solution in a hot water bath at 85°C to evaporate the solvent until a gel is formed, then drying the gel in a drying oven at 120°C for 10 hours to completely remove the solvent, and grinding to obtain a powder precursor;

[0046] 3) The above powder was placed in a tube furnace and heated at 4 °C min -1 The heating rate was raised to 700℃ and kept for 8h to obtain carbon-coated NASICON-type Na 3.6 MnCr 0.4 Ti 0.5 Mg 0.1 (PO 4 ) 3 Positive electrode material.

[0047] The Na prepared in Example 3 3.6 MnCr 0.4 Ti 0.5 Mg 0.1 (PO 4 ) 3 The positive electrode material was assembled into a CR2032 button cell according to the method in Example 1. + / Na), the first-week discharge capacity at 0.1C current density is 148.9 mAh g -1 After activation at 0.2C for 3 weeks and cycling at 0.5C for 50 weeks, the capacity retention rate was 90.8%.

[0048] Comparative Example 1

[0049] 1) Prepare a mixed solvent of 50 mL of deionized water and 25 mL of anhydrous ethanol, add 2 mmol of anhydrous citric acid, and stir until completely dissolved; take 1 mmol of manganese acetate tetrahydrate, 0.6 mmol of isopropyl titanate, and 0.4 mmol of cadmium nitrate nonahydrate, and add them to the above citric acid solution in sequence, and continue stirring for 30 minutes to dissolve and fully complex; then add 3.57 mmol of sodium acetate (molar excess of 5%) and 3 mmol of diammonium phosphate, and continue stirring for 60 minutes until a uniform solution is formed;

[0050] 2) Stirring the above solution in a hot water bath at 85°C to evaporate the solvent until a gel is formed, then drying the gel in a drying oven at 120°C for 10 hours to completely remove the solvent, and grinding to obtain a powder precursor;

[0051] 3) The above powder was placed in a tube furnace and heated at 4 °C min -1 The heating rate was raised to 700℃ and kept for 8h to obtain carbon-coated NASICON-type Na 3.4 MnCr 0.4 Ti 0.6 (PO 4 ) 3 Positive electrode material.

[0052] The Na prepared in Comparative Example 1 3.4 MnCr 0.4 Ti 0.6 (PO 4 ) 3 The positive electrode material was assembled into a CR2032 button cell according to the method in Example 1. + / Na), the first-week discharge capacity at 0.1C current density is 150.9 mAh g -1 After activation at 0.2C for 3 weeks and cycling at 0.5C for 50 weeks, the capacity retention rate was 90.1%.

[0053] In Comparative Example 1, z=0, and only three transition metals, Mn, Cr, and Ti, are contained. Compared with Example 1, both the capacity and the cycle stability are decreased.

[0054] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high specific energy and high stability manganese-based phosphate positive electrode material, characterized in that: The following steps are involved: 1) preparing a citric acid solution, adding the transition metal raw materials, i.e., a manganese source, a titanium source, a chromium source and a doped metal ion source, into the citric acid solution, and stirring for 20-40 minutes to completely dissolve and fully complex them; then adding a sodium source and a phosphorus source, and continuing stirring for 40-60 minutes to obtain a uniform solution; 2) Stirring the above solution in a hot water bath until a gel is formed, then placing the gel in a forced air drying oven to completely remove the solvent, and grinding to obtain a precursor powder; 3) placing the precursor powder in a tube furnace and calcining it at high temperature under the protection of an inert atmosphere to obtain the manganese-based phosphate positive electrode material.

2. The method for preparing the high specific energy and high stability manganese-based phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the solvent of the citric acid solution is a mixed solvent of deionized water and anhydrous ethanol, and the volume ratio of deionized water to anhydrous ethanol is 2:1; the stoichiometric ratio of citric acid to the transition metal element is (0.5-1.5):1; compared with the stoichiometric ratio in the chemical formula, the molar ratio of the sodium source is 3-5% in excess; the stoichiometric ratio of the phosphorus source to the transition metal element is 3:

2.

3. The method for preparing the high specific energy and high stability manganese-based phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the manganese source is at least one of manganese acetate, manganese nitrate, and manganese acetylacetonate; the titanium source is at least one of isopropyl titanate, tetraethyl titanate, and tetrabutyl titanate; the chromium source is at least one of chromium nitrate, chromium acetate, and chromium trioxide; the sodium source is at least one of sodium acetate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hydroxide, and sodium oxalate; the phosphorus source is at least one of diammonium phosphate and phosphoric acid; and the doped metal ion source is at least one of acetate, nitrate, sulfate, oxalate, chloride, carbonate, and organic salt of the corresponding metal.

4. The method for preparing the high specific energy and high stability manganese-based phosphate positive electrode material according to claim 3, characterized in that: The metal in the doping metal ion source is selected from one or more of Fe, Co, Ni, Mg, Ca, Zn, Cu, Al, Ga, and Zr.

5. The method for preparing the high specific energy and high stability manganese-based phosphate positive electrode material according to claim 1, characterized in that: In the step 2), the water bath temperature is 65-90° C.; the drying temperature is 110-130° C., and the drying time is 8-12 hours.

6. The method for preparing a high specific energy and high stability manganese-based phosphate positive electrode material according to claim 1, characterized in that: In step 3), the inert atmosphere is a mixture of one or more of argon and nitrogen; the calcination temperature is 700-800°C, and the heating rate is 2-8°C min -1 The calcination time is 5-12 hours, and then it is naturally cooled to room temperature and taken out.

7. A high specific energy and high stability manganese-based phosphate positive electrode material prepared by the method according to any one of claims 1 to 6.

8. The high specific energy and high stability manganese-based phosphate positive electrode material according to claim 7, characterized in that: The material is a carbon-coated NASICON type positive electrode material Na 4-a MnCr x Ti y M z (PO4)3, where M is Fe 2+ 、Co 2+ 、Ni 2+ Mg 2+ , Ca 2+ 、Zn 2+ , Cu 2+ 、Al 3+ , Ga 3+ 、Zr 4+ One or more of; 0.2≤x≤0.6; 0.4≤y≤0.8; 0<z≤0.1; x+y+z=1; 0.3≤a≤0.8。 9. Use of the high specific energy and high stability manganese-based phosphate positive electrode material according to claim 7 or 8 in sodium ion batteries.

10. The use according to claim 9, characterized in that: The positive electrode material Na 4-a MnCr x Ti y M z The electrode sheet made of (PO4)3, Super P conductive carbon or conductive carbon black, and the binder sodium carboxymethyl cellulose is used as the positive electrode of the sodium ion battery, and the metallic sodium is used as the counter electrode with a concentration of 1 mol L -1 5 vol% fluoroethylene carbonate was added to NaClO4 / propylene carbonate as the electrolyte, and glass fiber was used as the separator. The button battery with model CR2032 was assembled in a high-purity argon atmosphere glove box with water and oxygen contents less than 0.01 ppm.

Citation Information

Cited By

  • Lanthanum-based composite phosphorus removal material as well as preparation method and phosphorus removal method thereof

    CN121338720A

  • A zirconium-hafnium co-doped polyanion positive electrode material, a preparation method thereof, a positive electrode sheet, and a battery

    CN122716323A